PENGARUH MEDIA EDUKASI MONOPOLI (HEALTHPOLY) TERHADAP PENGETAHUAN TENTANG GAYA HIDUP REMAJA DALAM PENCEGAHAN DIABETES MELITUS - Beatrice Claresta Natasha Zebua (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Diabetes mellitus is one of the global health problems that is increasing in prevalence, including among adolescents. The unhealthy lifestyle of adolescents is a risk factor that needs to be addressed. One potential approach in prevention efforts is through health education. Monopoly media (Healthpoly) emerged as an attractive alternative media to deliver health information to adolescents. Objective: To develop monopoly media with PPE model and analyze the effect of Healthpoly media on knowledge about adolescent lifestyle in preventing diabetes mellitus at SMAN 5 Cimahi. Methods: This study used a quantitative approach with quasi-experimental method and media development Planning, Production, and Evaluation (PPE) model. The research subjects were selected by purposive sampling technique totaling 90 students of class X and XI located at SMAN 5 Cimahi held on May 29, 2024. Results: The media developed through the PPE model is monopoly media (Healthpoly). The average pretest was 77.72 with a good category and the average posttest was 97.71 with a good category but there was an average increase of 26%. Hasil analisis menggunakan Uji Wilcoxon dengan hasil menunjukkan p value 0,000. The results of the analysis using the Wilcoxon Test with the results showed a p value of 0.000. Conclusion: There is an effect of monopoly educational media (Healthpoly) on knowledge about adolescent lifestyle in the prevention of diabetes mellitus at SMAN 5 Cimahi. Recommendation: This study can be developed in further research by considering other health materials.